PERBEDAAN MOTIVASI BERPRESTASI MAHASISWA SEMESTER VII-A JALUR SELEKSI PBUD DENGAN MAHASISWA SEMESTER VII-B JALUR SELEKSI LOKAL PADA PRODI PG PAUD FKIP UNIVERSITAS RIAU - Wusono Indarto; Said Suhil Achmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
This research was intended to find out the disparity of motivation of achievement of the 7th term student selected out through PBUD selection and ones picked out through local selection at the study program of PG PAUD in FKIP UR. This paper was a comparative research that it compared the indicator and variable to agroup of respondents. The data was collected by using an instrument in form of serveyor, in where the serveyor was developed from a variable of motivation with three indicators. Indicator I: the risk taker consisted of 12 discriptors; Indicator II: ones who needed feedback consisted of 8 discriptors; and Indicator III: ones who considered succes consisted of 8 discriptors. The number of all discriptors was 28 units. After being tested for the validity, 4 of them were invalid. The population of this research was 94 student who 42 of them were the students from PBUD selection and the other 52 were from the local selection. The sample of the research was 64 students, 30 of them were from PBUD selection and the other were from the local selection. Based on the data collected, the score of motivation of achievement of the PBUD studends was 79.833 and percentage was 83.16%. The number of percentage was “very high” after being matched with criterion. While the score of local selected students was 76.4112 oe the number in percent was 79.63% which was considered in the level of high. While in the hypothesis of search testing with computer calculation, it was showed that there was a disparity of the motivation of the students selected through PBUD selection to the ones picked out through local selection at the study program of PG PAUD in FKIP UR. Based on the calculation of thitung, the result was 3.698327 higher than ttabel which was only <3.698327> 2.617 in the level of significance 0.01. Thus, Ho was rejected, which meant that there was a disparity of motivation on achievement of the 7th term students of PBUD selection and the students of local selection. Keyword: motivation of achievement